THE USE OF COOPERATIVE LEARNING TYPE ROUNDTABLE TECHNIQUE TO IMPROVE THE ABILITY OF THE SECOND YEAR STUDENTS OF SMAN 10 PEKANBARU IN WRITING HORTATORY EXPOSITION TEXT - Siregar, Verawati Fajrin; .K, Syafri; ', Hadriana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
The purpose of this classroom action research was to investigate the effectiveness ofcooperative learning type Roundtable technique in improving students’ ability inwriting hortatory exposition text at SMAN 10 Pekanbaru. The participants of thisresearch were 38 students of grade XI who had poor to average level of Englishproficiency. The data mainly gained from the writing test which was divided into pre-test and post-test. The findings indicated that Roundtable technique had a positive effecton the students’ writing ability particularly in each components of writing. It can beseen in the statistical analysis which showed that the mean score in the pre-test was43,9, increased to 60,85 in post-test 1 and 76,37 in post-test 2. It was revealed that theuse of Roundtable technique statistically improved students’ writing ability. Moreover,qualitative evidence showed that students within cooperative learning situation wereactually making meaning for themselves and others. This classroom situation helped theresearcher and the students conducted a creative, effective, and cooperative learningprocess. Roundtable technique was highly effective with creative writing and enjoyablebrainstorming activities. This structure encourages responsibility for the group andteam building.Keywords: Roundtable technique, writing ability, hortatory exposition text